Identifying the Effect of Mobile Operating Systems on the Mobile Services Market - Toshifumi Kuroda; Teppei Koguchi; Takanori Ida (International Telecommunications Society (ITS), 2017)
Modern economic theory predicts that tying can serve as a tool for leveraging market power. In line with this economic theory, competition authorities regulate the tying of Microsoft Windows with its Media Player or Internet browser in the EU and Japan. The authorities also take note of the market power of mobile handset operating systems (OSs) over competition in the app and services markets. However, no empirical evidence has thus far been presented on the success of government intervention in the Microsoft case. To assess the effectiveness of government intervention on mobile handset OSs, we identify the extent to which complementarity and consumer preferences affect the correlation between mobile handset OSs and mobile service app markets (mail, search, and map). We find significant positive complementarity between the mail, search, and map services, and mobile handset OSs. However, the elasticities of the mobile handset OS–mobile service correlations are rather small. We conclude that taking action to restrict mobile handset OSs is less effective than acting on mobile services market directly.
Keywords: L12; L43; L96; 330; Mobile phone; Handset; Internet service; Platform competition